Attenuated HIV-1 Nef But Not Vpu Function in a Cohort of Rwandan Long-Term Survivors - Umviligihozo, Gisele; Mann, Jaclyn K.; Jin, Steven W.; Mwimanzi, Francis M.; Hsieh, Hua-Shiuan A.; Sudderuddin, Hanwei; Lee, Guinevere Q.; Byakwaga, Helen; Muzoora, Conrad; Hunt, Peter W.; Martin, Jeff N.; Haberer, Jessica E.; et al. (Frontiers in Virology, 2022)
HIV-1 accessory proteins Nef and Vpu enhance viral pathogenesis through partially overlapping immune evasion activities. Attenuated Nef or Vpu functions have been reported in individuals who display slower disease progression, but few studies have assessed the relative impact of these proteins in non-B HIV-1 subtypes or examined paired proteins from the same individuals. Here, we examined the sequence and function of matched Nef and Vpu clones isolated from 29 long-term survivors (LTS) from Rwanda living with HIV-1 subtype A and compared our results to those of 104 Nef and 62 Vpu clones isolated from individuals living with chronic untreated HIV-1 subtype A from the same geographic area. Nef and vpu coding regions were amplified from plasma HIV RNA and cloned. The function of one intact, phylogenetically-validated Nef and Vpu clone per individual was then quantified by flow cytometry following transient expression in an immortalized CD4+ T-cell line. We measured the ability of each Nef clone to downregulate CD4 and HLA class I, and of each Vpu clone to downregulate CD4 and Tetherin, from the cell surface. Results were normalized to reference clones (Nef-SF2 and Vpu-NL4.3). We observed that Nef-mediated CD4 and HLA downregulation functions were lower in LTS compared to the control cohort (Mann-Whitney p=0.03 and p<0.0001, respectively). Moreover, we found a positive correlation between Nef-mediated CD4 downregulation function and plasma viral load in LTS and controls (Spearman ρ= 0.59, p=0.03 and ρ=0.30, p=0.005, respectively). In contrast, Vpu-mediated functions were similar between groups and did not correlate with clinical markers. Further analyses identified polymorphisms at Nef codon 184 and Vpu codons 60-62 that were associated with function, which were confirmed through mutagenesis. Overall, our results support attenuated function of Nef, but not Vpu, as a contributor to slower disease progression in this cohort of long-term survivors with HIV-1 subtype A.